Family Nutrition: A RECIPE for Good Communication - Larry Forthun; Matthew Kaplan (EDIS)
FCS-8670, a 5-page fact sheet by Larry Forthun and Matthew Kaplan, uses the “RECIPE” acronym to describe the ingredients for good communication about nutrition in the family: reflective listening, encouragement, compromise and cooperation, “I” messages, practice, and engagement. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2008.